2019
DOI: 10.3390/ijms20215374
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of PBCA Nanoparticles Loaded with Thymulin Against the Relapsing-Remitting Form of Experimental Autoimmune Encephalomyelitis in Mice

Abstract: Relapsing–remitting experimental autoimmune encephalomyelitis (rEAE) in mice is a model that closely resembles relapsing–remitting multiple sclerosis in humans. This study aims to investigate a new approach to modulation of the inflammatory response in rEAE mice using a thymic peptide thymulin bound to polybutylcyanoacrylate (PBCA) nanoparticles. PBCA nanoparticles were used to prolong the presence of thymulin in the blood. Cytokine levels in blood were measured by ELISA; NF-κB and SAPK/JNK cascade activation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…However, the most striking effect of thymulin was the normalization of JNK signaling. These results are consistent with data that thymulin is an important modulator in inflammations of various etiology, such as septic-type inflammations 10 or autoimmune diseases, 13 , 14 and with the findings on the possible role of thymulin in response to oxidative damage. 25 The study have some limitations.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, the most striking effect of thymulin was the normalization of JNK signaling. These results are consistent with data that thymulin is an important modulator in inflammations of various etiology, such as septic-type inflammations 10 or autoimmune diseases, 13 , 14 and with the findings on the possible role of thymulin in response to oxidative damage. 25 The study have some limitations.…”
Section: Discussionsupporting
confidence: 93%
“…The immunomodulatory and anti-inflammatory effect of thymulin was previously shown in mice with septic-type inflammation 11 , 12 and in mice with experimental autoimmune encephalomyelitis. 13 , 14 Furthermore, our previous study showed beneficial effects of PRDX6 in RIN-m5F β-cells in vitro 15 and of thymulin in mice with diabetes induced by alloxan administration in vivo. 16 , 17 In addition, a significant stimulatory effect of PRDX6 on the insulin-producing activity of pancreatic β-cells was demonstrated, and, most importantly, the effect of PRDX6 was detected during culturing the cells under both normal and diabetes-modeling conditions.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Lunin et al [106] developed poly(butylcyanoacrylate) (PBCA) nanoparticles, in order to deliver the thymic peptide thymulin and prolong its presence in the blood of mice with relapsing/remitting EAE (rEAE). The increase in the blood content of thymulin, which is depleted with age, and the prolongation of its blood half-life, alone or in combination with other treatments, may be a prospective strategy for treatment of chronic inflammatory conditions, such as MS. More analytically, as revealed by the results, thymulin significantly decreased symptoms of rEAE and lowered plasma cytokine levels, both in early and in later stages of rEAE, as well as decreased the NF-κB and stress-activated protein kinase/Jun amino-terminal kinase (SAPK/JNK) cascade activation, as confirmed by ELISA measurements of cytokine levels in the blood.…”
Section: Other Polymeric Nanoparticlesmentioning
confidence: 99%
“…Thymulin and other thymic peptides, in fact, are characterized by their very low half-life in plasma (less than 10 min) and in vivo data show that orally administered poly-butylcyanoacrylate (PBCA) nanoparticles containing the thymic hormone thymopentin had similar effects to intravenous thymopentin, but with enhanced bioavailability due to the nanoparticles [6].…”
mentioning
confidence: 99%